ParticleHolography.jl: Holographic particle measurement in Julia - Dai Nakai; Yohsuke Tanaka (SoftwareX)
ParticleHolography.jl is an open-source Julia package designed for particle measurements using in-line holography. This comprehensive software provides an end-to-end processing pipeline encompassing a wide range of functionalities: preprocessing, including background removal and camera calibration; three-dimensional reconstruction through diffraction calculations; particle analysis, including detection and tracking; and result visualization. Leveraging the Julia language architecture and NVIDIA GPU capabilities, the package accommodates both interactive parameter exploration and optimization as well as intensive, large-scale data processing across multiple nodes. The modular pipeline structure allows for easy substitution of processing steps with alternative or user-defined methods, facilitating ablation analysis and customization. ParticleHolography.jl aims to contribute to the advancement of research and industry by serving as a versatile in-line holography-based platform for three-dimensional multi-object detection and tracking. Its applications span diverse fields, including fluid dynamics, biology, and aerosol engineering.